Vitamin D, calcium or a combination of vitamin D and calcium for the treatment of nutritional rickets in children - Chibuzor, Moriam T (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of vitamin D, calcium or a combination of vitamin D and calcium for the treatment of nutritional rickets in children.